Primrose Pearl Corporation - Peter George Mathew, Annabelle Florentia; Liudin, Lailatul Nashuha; Suharto, Muhammad Nur Patra; Mohammad Yassim, Nurain Ashyqin; Willie, Wellonica Olga (2015)
Nowadays, people are having very little time to prepare themselves before doing something or going somewhere. Their time is also very limited, disabling them from arriving early to classes or works, and even restraining them from getting things done, due to insufficient time. Usually, they are having trouble preparing themselves early, since grooming processes always take very long period of time to finish, especially during bathing. For example, washing hair might be the bane during the whole processes, since it takes up to 10 minutes to be done, causing distress early in the morning. Therefore, our company, Primrose Pearl Corporation, wants to help them to get prepared easily before they have to face the day's challenges. Our product, Gisele, an antidandruff dry shampoo will help our customers to save their time, hence, increasing their daily productivities. Normally, washing hair using regular shampoo takes so long to be finished, since they have to use the conditioner after washing their hair, before rinsing it thoroughly using water, taking up to 10 minutes to complete. Our company wants to help them save a significant amount of their time for them, since our product may save 80% of their time, whereby it only takes 2 minutes to complete the task, even without using any water. Besides that, our company is also trying to answer the market's demand, since there are still no anti-dandruff dry shampoo sold in the market. The only dry shampoos that can be found are the normal ones, without carrying the aspect of preventing one's hair from dandruffs. A lot of feedbacks has been received by the shops selling them, whereby they stated that the regular dry shampoos that are being sold in the shops do not help them with their problems, causing the demand for anti-dandruff dry shampoos to exist. Hence, causing the establishment of our company and the creation of our newly-developed product.